2023
DOI: 10.1371/journal.pone.0282539
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma presentation and prognosis among Nigerian adults with and without HIV

Abstract: Introduction Hepatocellular carcinoma (HCC) is an increasing cause of mortality in Nigeria among persons with HIV (PLH), as access to antiretroviral therapy (ART) improves. In this study we describe clinical, radiological, and laboratory characteristics in Nigerian adults with HCC, with and without HIV, and examine how HIV impacts survival. Methods This prospective observational study was conducted between August 2018 and November 2021 at two Nigerian hospitals [Jos University Teaching Hospital (JUTH) and La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In another study, HBsAg carriage was lower 50% [ 19 ], which could be due to the small sample size. Studies performed in Senegal, Ghana and Nigeria reported hepatitis B positivity rates of 69.5%, 75.2% and 52%, respectively, in HCC patients [ 20 22 ]. This confirms hepatitis B as a major risk factor for HCC in The Gambia and the subregion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, HBsAg carriage was lower 50% [ 19 ], which could be due to the small sample size. Studies performed in Senegal, Ghana and Nigeria reported hepatitis B positivity rates of 69.5%, 75.2% and 52%, respectively, in HCC patients [ 20 22 ]. This confirms hepatitis B as a major risk factor for HCC in The Gambia and the subregion.…”
Section: Discussionmentioning
confidence: 99%